CHALLENGES OF ACADEMIC RESAERCH IN GHANA: VIEWS FROM KOFORIDUA POLYTECHNIC, GHANA - Owusu-Acheaw, Michael; Asante, Edward (IJRDO - Journal of Social Science and Humanities Research, 2016)
The research was largely guided by qualitative paradigm based on the assessment of the views on the challenges of research among the academic staff at Koforidua Polytechnic, Ghana. The focal group discussion method was adopted throughout the research process. The views of participants were centered on issues of challenges of academic, attitude towards research, interest in academic research, frequency of publication and possible measures to mitigate the challenges of academic research. A Total of 110 participants took part in a workshop organized for academic staff of Koforidua Polytechnic on research and scholarly publication in April; 2015.The views obtained showed that research publication among academia is associated with challenges. Also a considerable number of the academic staff has a lukewarm attitude towards research resulting in low frequency of publishing. However, there was evidence of high interest in research activities in the polytechnic under review